Question 1:
F(x) and g(x) are like variables, just plug into the equation.
f(x) + g(x) = (x + 6) + (12x - 7)
x+6+12x-7 = 13x-1
Question 2: f(3) + g(-1)
You plug in the x-values into the equation, and then take the answer and add them together.
f(3) = 3+4
g(-1) = 12(-1)-6
f(3) = 7
g(-1) = -18
7 + (-18) = -11
Question 3:
This is similar to question 1, plug in the variables and simplify.
9x - (7x+3)
Remember to distribute the "-"
9x - 7x - 3
2x - 3
Answer:
Remainder= 5, and the binomial is not a factor of the given polynomial.
Step-by-step explanation:
Given polynomial is , we have to divide this with a binomial [tex}(x-1)[/tex] using remainder theorem.
Remainder theorem says if is a factor then remiander would be
Therefore for
Thus the remainder is 5 and since it is not 0 , so the binomial is not a factor of the given polynomial.
Answer:
600 m³
Step-by-step explanation:
The shape we have is a rectangular pyramid:
Formula:<u><em> (volume of a rectangular pyramid)</em></u>
Volume = (1/3) × Base Area × height
___________________________
In our case :
Base area = L × W = 20 × 18 = 360 m²
height = 5 m
⇒ Volume = (1/3) × Base Area × height
Answer:
No they are only there so u can understand and answer the questions